DAMPAK MEDIA INSTAGRAM DAN KUALITAS PRODUK PADA MINAT PEMBELIAN FROZEN EMPAL - Sheila Rosalind Soeprapto; Tina Melinda (STIE Mahardhika, 2019)
This study aims to examine the influence of Instagram promotion and product quality on the purchase intention of Bibik Empal. This study employs purposive sampling to select 115 people as samples from the research population, which consists of Bibik Empal daily catering consumers. Multiple Linear Regression is used as data analysis technique with the help of SPSS software. Research results indicate that Instagram and product quality significantly affect the purchase intention of Bibik Empal, both partially and simultaneously.